HUBUNGAN TINGKAT PENGETAHUAN IBU PRIMIPARA TENTANG IMUNISASI DENGAN KELENGKAPAN IMUNISASI DI POSYANDU KALIPUTIH PUSKESMAS SEMPOR I - nendarwati, resni; -, handoyo; qomar, umi laelatul (Jurnal Ilmiah Kesehatan Keperawatan, 2010)
Immunization is one of preventive action to keep community healthy. This program is shown preventive action to prevent some deceases. The role of mother is very important to be successfully this program. This situation should be supported by knowledge about immunization for mother. The objective of the research was to find out correlations between knowledge level of primipara about immunization and accomplishment of immunization in Posyandu Kaliputih Community Health Center I Sempor. Populations were taken by using accidental sampling to the family who had baby in community health center I Sempor. There were 32 respondents as the samples. The research used cross sectional approach where the researcher only described correlations between knowledge level of primipara about immunization and accomplishment of immunization in Posyandu Kaliputih Community Health Center I Sempor. The data were collected by using check list questionnaire consisted of 20 questions about knowledge level of immunization, and observed letter for knowing accomplishment of immunization. The result finding showed that, p value=0,010 dan (x²) count = 9,224 and taken by chi square test. There are correlations between knowledge level of primipara about immunization and accomplishment of immunization in Posyandu Kaliputih Community Health Center I Sempor Keywords; knowledge, primipara, imunization, immunization